2017
DOI: 10.3847/1538-4357/aa8305
|View full text |Cite
|
Sign up to set email alerts
|

Freely Expanding Knots of X-Ray-emitting Ejecta in Kepler’s Supernova Remnant

Abstract: We report measurements of proper motion, radial velocity, and elemental composition for 14 compact X-ray bright knots in Kepler's supernova remnant (SNR) using archival Chandra data. The highest speed knots show both large proper motions (µ ∼ 0.11-0.14 yr −1 ) and high radial velocities (v ∼ 8,700-10,020 km s −1 ). For these knots the estimated space velocities (9,100 km s −1 v 3D 10,400 km s −1 ) are similar to the typical Si velocity seen in SN Ia near maximum light. High speed ejecta knots appear only in sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…A model consisting of a power law + several Gaussian models + background model fits the spectrum well (χ 2 /d.o.f = 42.16/55), and we found the spectrum has strong Kshell emission from the Fe-peak elements (Cr, Mn, Fe, Ni) where the significance for each element is above 2σ ( Table 1). The centroid energies of all the lines are slightly higher (∼30-70 eV) than those in the remnant as a whole (Park et al 2013), consistent with a spectrum blueshifted by several thousand km s −1 as reported in Sato & Hughes (2017b). As we show below, spectral fits using a physical NEI model also require a comparable blueshift for the Fe-rich knot.…”
Section: Observations and Analysissupporting
confidence: 86%
See 2 more Smart Citations
“…A model consisting of a power law + several Gaussian models + background model fits the spectrum well (χ 2 /d.o.f = 42.16/55), and we found the spectrum has strong Kshell emission from the Fe-peak elements (Cr, Mn, Fe, Ni) where the significance for each element is above 2σ ( Table 1). The centroid energies of all the lines are slightly higher (∼30-70 eV) than those in the remnant as a whole (Park et al 2013), consistent with a spectrum blueshifted by several thousand km s −1 as reported in Sato & Hughes (2017b). As we show below, spectral fits using a physical NEI model also require a comparable blueshift for the Fe-rich knot.…”
Section: Observations and Analysissupporting
confidence: 86%
“…Proper motions at the northern rim of Kepler's SNR show values of ∼0.8-0.11 yr −1 (Katsuda et al 2008;Vink 2008) corresponding to speeds of 2,300-3,100 km s −1 at the distance of 6 kpc (e.g., Millard et al 2019). The 3D velocities of associated knots SW1 and SW2 from Sato & Hughes (2017b) are ∼5,000-8,000 km s −1 , significantly higher than the expansion velocity of the northern rim. We can estimate the 3D position of the Fe-rich structure from the explosion center, R 3D as…”
Section: How To Create Fe-rich Clumpy Ejectamentioning
confidence: 78%
See 1 more Smart Citation
“…For spectral fitting purposes (Section 3.3), we reprocessed the six ObsIDs from the 2006 archival ACIS-S3 data by following standard data reduction procedures with CIAO versions 4.8 to 4.8.2 and CALDB version 4.7.2, which resulted in a total effective exposure of ∼ 733 ks. To make our proper motion measurements, we used the 2000, 2006, and 2014 archival Chandra ACIS data, as previously processed and prepared in Sato & Hughes (2017b). Chandra HETG 3-color image of Kepler.…”
Section: Observationsmentioning
confidence: 99%
“…A straightforward way to reveal the 3-D structure of ejecta, and ultimately the explosion nature and dynamical evolution of Kepler, is to measure the Doppler shifts in the emission lines from the X-ray-emitting ejecta knots projected over the face of the SNR, and thus their bulk motion radial velocities (v r ) along the line of sight. Recently, Sato & Hughes (2017b) reported measurements of radial velocity for several compact X-ray-bright knots in Kepler's SNR using archival Chandra ACIS data. They measured high radial velocities of up to ∼ 10 4 km s -1 and nearly free expansion rates for some knots.…”
Section: Introductionmentioning
confidence: 99%